A new automated method for high‐throughput carbon and hydrogen isotope analysis of gaseous and dissolved methane at atmospheric concentrations. (6th May 2021) - Smith, Andrew C.; Welsh, Steve; Atkinson, Helen; Harris, David; Leng, Melanie J.
Abstract : Rationale: The dual isotope ratio analysis, carbon (δ 13 C value) and hydrogen (δ 2 H value), of methane (CH4 ) is a valuable tracer tool within a range of areas of scientific investigation, not least wetland ecology, microbiology, CH4 source identification and the tracing of geological leakages of thermogenic CH4 in groundwater. Traditional methods of collecting, purification, separating and analysing CH4 for δ 13 C and δ 2 H determination are, however, very time consuming, involving offline manual extractions. Methods: Here we describe a new gas chromatography, pyrolysis/combustion, isotope ratio mass spectrometry (IRMS) system for the automated analysis of either dissolved or gaseous CH4 down to ambient atmospheric concentrations (2.0 ppm). Sample introduction is via a traditional XYZ autosampler, allowing either helium (He) purging of gas or sparging of water from a range of suitable, airtight bottles. Results: The system routinely achieves precision of <0.3‰ for δ 13 C values and <3.0‰ for δ 2 H values, based on long‐term replicate analysis of an in‐house CH4 /He mix standard (BGS‐1), corrected to two externally calibrated reference gases at near atmospheric concentrations of methane. Depending upon CH4 concentration and therefore bottle size, the system runs between 21 (140‐mL bottle) and 200 samples (12‐mL exetainer) in an unattended run overnight. Conclusions: This represents the first commercially available IRMS system for dual δ 13 C and δ 2 H analysis of methane at atmospheric concentrations and a step forward for the routine (and high‐volume) analysis of CH4 in environmental studies.